2009
DOI: 10.1128/iai.00470-08
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Linear Peptide Chimeric Vaccine-Induced Antimalaria Immunity Is Associated with Enhanced In Vitro Antigen Loading

Abstract: Immunization of mice with Plasmodium berghei or Plasmodium yoelii synthetic linear peptide chimeras (LPCs) based on the circumsporozoite protein protects against experimental challenge with viable sporozoites. The immunogenicity of LPCs is significantly enhanced by spontaneous polymerization. To better understand the antigenic properties of polymeric antimalarial peptides, we studied the immune responses elicited in mice immunized with a polymer or a monomer of a linear peptide construct specific for P. yoelii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Three factors could explain the improved cellular immunogenicity of our construct: (1) The defined P. vivax promiscuous T cell epitopes, specially PvT53 and PvT19, have been shown to increase the immunogenicity of diverse antigens, as closely related as the P. falciparum CSP (NANP) 3 repeats 24 , or as far as B cell epitopes of the Tau and Amyloid-Beta proteins related to Alzheimer disease 51 . (2) We have shown the ability of our chimeric proteins with the topology used for the design of PvRMC-MSP1 to enhance dendritic cells uptake and maturation 52 . (3) Our promiscuous T cell epitopes resemble a family of compounds that are known as cell penetrating peptides (CPPs) 52 .…”
Section: Discussionmentioning
confidence: 94%
“…Three factors could explain the improved cellular immunogenicity of our construct: (1) The defined P. vivax promiscuous T cell epitopes, specially PvT53 and PvT19, have been shown to increase the immunogenicity of diverse antigens, as closely related as the P. falciparum CSP (NANP) 3 repeats 24 , or as far as B cell epitopes of the Tau and Amyloid-Beta proteins related to Alzheimer disease 51 . (2) We have shown the ability of our chimeric proteins with the topology used for the design of PvRMC-MSP1 to enhance dendritic cells uptake and maturation 52 . (3) Our promiscuous T cell epitopes resemble a family of compounds that are known as cell penetrating peptides (CPPs) 52 .…”
Section: Discussionmentioning
confidence: 94%
“…Some of the perceived major arguments against the peptide-based vaccine approach include their short linear nature that prohibited the inclusion of multiple protective B-cell and T-cell epitopes in the same construct and the presumed inability to create the Cys-Cys disulfide bonds in conformationdependent epitopes. However, recent studies suggest that protein domains that mimic the native protein structure can be created in chemically synthesized peptide constructs that include conformationally correct Cys-Cys bonds to create immunologically active molecules (7,48,49). In addition, recently it has been suggested that large-scale and costeffective synthesis of peptide-based vaccines is possible (8).…”
mentioning
confidence: 99%
“…We have previously shown that positively charged polymeric synthetic peptide constructs (PvRMC-CSP exhibits an isoelectric point of 9.39) are internalized by antigenpresenting cells via endocytosis (67). In this work, peptide uptake was enhanced by the interaction of positively charged residues with negatively charged membranes similar to the mechanism used by a family of compounds called cell-penetrating peptides.…”
Section: Discussionmentioning
confidence: 85%
“…In this work, peptide uptake was enhanced by the interaction of positively charged residues with negatively charged membranes similar to the mechanism used by a family of compounds called cell-penetrating peptides. The endocytosis of these peptides upregulated cytokine production and expression of cell surface maturation markers by DCs and ultimately was related to protection in mice against a P. yoelii challenge (67).…”
Section: Discussionmentioning
confidence: 99%